New Approach of UAV Movement Detection and Characterization Using Advanced Signal Processing Methods Based on UWB Sensing - Angela Digulescu; Cristina Despina-Stoian; Denis Stănescu; Florin Popescu; Florin Enache; Cornel Ioana; Emanuel Rădoi; Iulian Rîncu; Alexandru Șerbănescu (Sensors, 2020)
In the last years, the commercial drone/unmanned aerial vehicles market has grown due to their technological performances (provided by the multiple onboard available sensors), low price, and ease of use. Being very attractive for an increasing number of applications, their presence represents a major issue for public or classified areas with a special status, because of the rising number of incidents. Our paper proposes a new approach for the drone movement detection and characterization based on the ultra-wide band (UWB) sensing system and advanced signal processing methods. This approach characterizes the movement of the drone using classical methods such as correlation, envelope detection, time-scale analysis, but also a new method, the recurrence plot analysis. The obtained results are compared in terms of movement map accuracy and required computation time in order to offer a future starting point for the drone intrusion detection.